2006
DOI: 10.1593/neo.06634
|View full text |Cite
|
Sign up to set email alerts
|

The Proteasome Inhibitor MG-132 Protects Hypoxic SiHa Cervical Carcinoma Cells after Cyclic Hypoxia/Reoxygenation from Ionizing Radiation

Abstract: Proteasome inhibition radiosensitizes oxygenated tumor cells but may also protect tumor cells from ionizing radiation under certain hypoxic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Further, recent reports demonstrate proteasome inhibitor-induced activation of EGFR as well as EGFR-independent mechanisms can induce MAPK, AKT and STAT3 prosurvival pathways, as observed here. 9,19, 32-34 Additionally, while proteasome inhibitors radiosensitized cancer cells and smaller xenograft tumors in experimental models, 15-17 they may enhance radioprotection of SCC tumor cells under hypoxic conditions, 35 such as occur in large SCCHN in advanced stage patients. Cytokines and angiogenesis factors expressed by SCCHN in response to prosurvival 26 and hypoxia signals 36 were detected in serum of all 7 patients pretreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Further, recent reports demonstrate proteasome inhibitor-induced activation of EGFR as well as EGFR-independent mechanisms can induce MAPK, AKT and STAT3 prosurvival pathways, as observed here. 9,19, 32-34 Additionally, while proteasome inhibitors radiosensitized cancer cells and smaller xenograft tumors in experimental models, 15-17 they may enhance radioprotection of SCC tumor cells under hypoxic conditions, 35 such as occur in large SCCHN in advanced stage patients. Cytokines and angiogenesis factors expressed by SCCHN in response to prosurvival 26 and hypoxia signals 36 were detected in serum of all 7 patients pretreatment.…”
Section: Discussionmentioning
confidence: 99%
“…The proteasome inhibitor MG132 increases p53 protein levels and transcriptional activity in human cervical cancer cell lines, providing for sensitization of the cells to TRAIL-receptor or Fas-mediated apoptosis [84] or radiosensitivity under hypoxic conditions [85]. Bortezomib (PS341, Velcade ® , Millennium Pharmaceuticals, Cambridge, MA, USA), with specificity for the chymotrypsin-like proteasome activity [86], has been shown to sensitize SiHa to radiotherapy via inhibition of the NF-ĸB pathway, in tumor xenografts induces caspase 3 cleavage and under hypoxic conditions decreases vascular endothelial growth factor (VEGF) production, affecting tumor growth [87,88].…”
Section: Development Of Novel Treatmentsmentioning
confidence: 99%
“…Moreover, a recent study showed that glioma stem cells are resistant to proteasome inhibitors [173], further suggesting that proteasome inhibitors have only limited use in the radiotherapy of gliomas. However, the extent of sensitization of cells by proteasome inhibitors (possibly in combination) from cytotoxic agents may depend on the sequence of application [174] and the microenvironment [175]. Given the limited number of preclinical studies performed on this particularly challenging malignancy, it is too early to rule out the possibility that the right drug administration schedule, dose and optimal drug combinations could lead to potential improvement in glioma therapy.…”
Section: Marizomib In Preclinical Solid Tumor Modelsmentioning
confidence: 99%